2022
DOI: 10.3390/coatings12101461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Mechanical Properties of 316 LN Austenitic Stainless Steel

Abstract: The microstructure development of 316 LN austenitic stainless steel (316 LNSS) during the aging process is investigated in this article. The thermal aging processes were conducted at 750 °C with different periods ranging from 50 to 500 h. The metallographic results show that the coherent and incoherent twins were present in the original 316 LNSS grains, but dwindled as the aging period increased. After 50 h of aging, many fine, dispersed particles precipitated from the matrix, which were identified as M23C6 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…It can be observed from the microscopic images that when 0.35 of Ti and Mn were added to stainless steel, the grain size in the microstructure became smaller, and when the amount of alloying elements (Ti and Mn) was increased to 0.75 and 1.5, an increase in the grain size was observed. Moreover, upon examination of Figures 3 and 4, which depict optical micro-scope and SEM microstructure images taken from all compositions of 316 L that were produced, it can be observed that twin structures have formed, consistent with similar findings in the literature [17][18][19]. grain size was observed.…”
Section: Microstructure Results and Evaluationsupporting
confidence: 88%
See 1 more Smart Citation
“…It can be observed from the microscopic images that when 0.35 of Ti and Mn were added to stainless steel, the grain size in the microstructure became smaller, and when the amount of alloying elements (Ti and Mn) was increased to 0.75 and 1.5, an increase in the grain size was observed. Moreover, upon examination of Figures 3 and 4, which depict optical micro-scope and SEM microstructure images taken from all compositions of 316 L that were produced, it can be observed that twin structures have formed, consistent with similar findings in the literature [17][18][19]. grain size was observed.…”
Section: Microstructure Results and Evaluationsupporting
confidence: 88%
“…grain size was observed. Moreover, upon examination of Figures 3 and 4, optical micro-scope and SEM microstructure images taken from all composi that were produced, it can be observed that twin structures have formed, co similar findings in the literature [17][18][19]. It was also observed that there are pores in the fine structure of the sam portion of which increases with the increase in the proportion of added alloy and these pores have a spherical and small shape.…”
Section: Microstructure Results and Evaluationsupporting
confidence: 84%
“…In contrast, the HT4 and HT5 specimens displayed microhardness drops to average HV0.05 values slightly higher than those registered for the other heat treatments; due to the long-time aging treatment, a fine precipitation of M 23 C 6 carbides may occur, increasing the hardness of the AISI 316L substrate [59,60]. Similar trends were found for the microhardness profiles measured in the heattreated specimens, but with slight differences according to the adopted heat treatment routes.…”
Section: Hardness Behaviorsupporting
confidence: 67%
“…In contrast, the HT4 and HT5 specimens displayed microhardness drops to average HV0.05 values slightly higher than those registered for the other heat treatments; due to the long-time aging treatment, a fine precipitation of M23C6 carbides may occur, increasing the hardness of the AISI 316L substrate [59,60].…”
Section: Hardness Behaviormentioning
confidence: 62%